Compatibility Study of Trichoderma Isolates with Chemical Fungicides - Manandhar, S.; Timila, R.D.; Karkee, A.; Gupt, S.K.; Baidya, S. (Journal of Agriculture and Environment, 2020)
Chemical use in agricultural farming in recent years has led to many threats concerning the environment and human health. Trichoderma spp. has been used as a biocontrol agent and is gaining popularity in recent years. Integrated use of Trichoderma with compatible chemicals is one disease management strategy which would aid in immediate action on plant pathogens and provide control over pathogens in long term as well. In vitro compatibility test of five Trichoderma isolates with thirteen different chemical fungicides at two different concentrations was carried out in the laboratory of Plant Pathology Division. The results showed that four of the tested chemical pesticides viz; Bavistin (Carbendazim 50% WP), Cryzole (Hexaconazole 5% SC), Benlate (Benomyl 50% WP) and Saaf (Carbendazim 12% Mancozeb 63% WP) exhibited complete inhibition of Trichoderma, irrespective of the isolates tested. Seven of them were compatible with all Trichoderma isolates and two chemicals Krilaxyl (Metalaxyl 8% + Mancozeb 64% WP) and Aver up (Chlorothalonil 75% WP) showed some degree of inhibition of two Trichoderma isolates, while the rest of the isolates were fully compatible. In all the chemical treatments it was noted that growth of Trichoderma decreased as the concentration of pesticides increased. Integration of safer and compatible chemical pesticides and Trichodermacan provide an effective and long-term solution against plant diseases in agricultural farming.